Editorial (2010)
With this edition we complete ten years of publication. What has the publication of your article(s) in profile meant to you? Publishing is a motivation for one to keep up-to-date, on the one hand, and a personal challenge to be academically active, on the other. Each publication has been an opportunity to have a long-term connection with others to tell them about my concerns in teaching and to let them know that despite “bad publicity”, we language teachers (at public schools) are doing much more than repeating lessons prepared by others. We are thinking about contextualised proposals as well as also reflecting about the consequences of our everyday interaction with pupils; we do care about the impact of education policies in the development of school life, thus, we are in a permanent struggle between our dreams and our realities (Myriam, inservice teach er, Colombia).